The influence of rockmass properties at the plastic zone around a circular tunnel - Antoniou, A.; Spyropoulos, I. (Bulletin of the Geological Society of Greece, 2013)
The influence of rockmass properties at the plastic zone around a circular tunnel. Tunneling in weak rock has to be carefully designed since the overestimation of weak rock mass properties or the underestimated design and behaviour of the support system can lead to increased cost or even to failure. Based on the generalized Hoek-Brown failure criterion this paper presents relation between geometrical parameters (tunnel's radius, depth, etc) and rock's mass parameters (GSI, mi, etc) with the extension of plastic zone around a circular tunnel, as well as the wall displacement of an unsupported circular tunnel. All the analyses were executed considering hydrostatic stress field and isotropic behaviour of the surrounding rock mass